2006
DOI: 10.1007/s11135-005-6105-z
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Surveys, Attitude Accessibility and the Effect on Respondents’ Susceptibility to Nonresponse

Abstract: Abstract. This paper analyzes whether respondents' attitudes toward surveys explains their susceptibility to item nonresponse. In contrast to previous studies, the decision to refuse to provide income information, not to answer other questions and the probability of 'don't know' responses is tested separately. Furthermore, the interviewers' overall judgments of response willingness was included as well. Respondents with a positive and cognitively accessible attitude toward surveys were expected to adopt a coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 38 publications
1
26
0
3
Order By: Relevance
“…Panel commitment and fatigue can also be measured more directly by asking respondents' attitude toward the panel survey (Rogelberg et al 2001;Stocké 2006). Whether a respondent attributes ''value'' to his or her own answers or ''enjoys'' it indicate that commitment is present.…”
mentioning
confidence: 99%
“…Panel commitment and fatigue can also be measured more directly by asking respondents' attitude toward the panel survey (Rogelberg et al 2001;Stocké 2006). Whether a respondent attributes ''value'' to his or her own answers or ''enjoys'' it indicate that commitment is present.…”
mentioning
confidence: 99%
“…Closeness to the LISS panel and attitudes towards surveys are included in the analysis as control variables because Stocké (2006) mentions the impact of sample persons' survey attitudes on the willingness to participate and item nonresponse. Concerning item nonresponse, Stocké (2006: 283) found that "attitudes alone were not a statistically significant predictor for nonresponse", but under the circumstance that "response latencies and thus the accessibility of the attitude answers were additionally taken into account".…”
Section: Independent/exogenous Variablesmentioning
confidence: 99%
“…For each subscale, I summarise the corresponding three items in an additive scale after having recoded reversed coded items. 75 One item of each subscale ("Surveys are interesting in themselves", "Surveys are important for society", "It is exhaustive to answer so many questions in a survey") is based on a suggestion by Stocké (2006). 74 Tests on the reliability and validity of a shortened scale confirm reliability, congruent validity and content validity of the scale.…”
Section: Panel Members' Personality Characteristicsmentioning
confidence: 99%
“…Past studies have identified consistent correlates with DK responses, and respondents with certain characteristics are found to be more likely t o g i v e D K r e s p o n s e s t h a n o t h e r s i n a t t i tudinal and opinion surveys. In particular, researchers have found that females, nonwhites, low-educated, low-income, and noninvolved respondents with feelings of low political efficacy give a predictably high number of DK responses (Francis and Busch, 1975;Faulkenberry and Mason, 1978;Pickery and Loosveldt, 1998;Singer et al, 2000;Krosnick et al 2002;Stocke, 2006).…”
Section: Non-substantive Responses In Survey Researchmentioning
confidence: 99%